Tuberization in vitro of Solanum tuberosum L. var. "Cochacina" with purple pulp - Segundo E. López Medina; José Mostacero León; Armando E. Gil Rivero; Angélica López Zavaleta; Anthony J. De La Cruz Castillo; Luigi Villena Zapata; Juan Amaro Villacorta Vásquez; Wilson Arcenio Maco Vásquez (Ciencia y Tecnología Agropecuaria, 2023)
This article seeks to establish the prospects for the valorization of 9 seeds and 12 fruit peels based on their physical properties. These residues were characterized with respect to: residue generation index (RGI), particle size, thickness, sphericity, density (particle and bulk), total moisture, hardness and maturity (color scale). By analyzing the results of these physical characteristics, the possibilities of utilization for obtaining edible foods, flours, pigments, composting, oil extraction and activated carbon were established. It was found that the IGR of shells and seeds was between 11.91-55.61 % and 2.08-13.95 %, respectively. Seeds presented particle sizes of 0.38-4.21 cm, sphericities between 0.42-0.90, particle density of 0.91-1.43 g/mL, bulk densities between 0.85-1.08 g/mL and total moisture of 31.42-84.71 %; while the shells presented thicknesses of 0.08-0.80 cm, densities between 0.94-1.19 g/mL, hardnesses from 54.49 N to values greater than 118.43 N and total moisture content of 15.19-94.44 %. It is concluded that shells are generated in greater quantity than seeds and it is recommended to use these residues together. In addition, the physical characteristics of the residues affect the alternative of utilization and valorization. Therefore, fruit residues can be used to obtain edible foods, flours, pigments, biofertilizers, vegetable oils and activated carbon; and it is recommended to perform other analyses such as: thermogravimetric, elemental, calorific value, bromatological, determination of adsorption curves and porosity, to revalidate the possibilities of utilization and valorization mentioned above.